2m - 3(9m + 1) = 7m + 4(7 + 5m)
2m - (27m + 3) = 7m + (28 + 20m)
2m -27m -3 =7m +28 +20m
- 25m - 3 = 27m + 28
- 25m - 27m = 28 + 3
- 52m = 31
52m = -31
m = - 31/52
2006-11-06 12:39:15
·
answer #1
·
answered by ju 2
·
0⤊
0⤋
2m - 3(9m + 1) = 7m + 4(7 + 5m)
Distribute
2m - 27m - 3 = 7m + 28 + 20m
Like Terms
-25m - 3 = 27m + 28
Add 3 on each side
-25m = 27m + 31
Subtract 27m on each side
-52m = 31
Divide by -52 on each side
m = -31/52
2006-11-06 12:26:59
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
2m - 3(9m+1) = 7m + 4(7+5m)
2m - 27m + 3 = 7m + 28 + 20m
25m + 3 = 27m + 28
-25m -25m
3= 2m + 28
-28 -28
-25 = 2m
m = -12.5
I didn't check it, but I'm pretty sure thats how you'd solve it.
2006-11-06 12:25:08
·
answer #3
·
answered by chattyshan24 1
·
0⤊
0⤋
2m - 3(9m + 1) = 7m + 4(7 + 5m)
2m - 27m - 3 = 7m + 28 + 20m
- 25m - 3 = 27m + 28 add 27m to each side =
2m - 3 = 28 add 3 to each side =
2m = 25 divide each side by 2 =
m = 13.5
2006-11-06 12:22:56
·
answer #4
·
answered by ? 5
·
0⤊
0⤋
2m - 3(9m + 1) = 7m + 4(7 + 5m)
2m - 27m - 3 = 7m + 28 + 20m
-25m - 3 = 27m + 28
-25m = 27m + 28 + 3
-25m - 27m = 31
-52m = 31
m = -31/52
2006-11-06 12:15:13
·
answer #5
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
2m - 27m - 3 = 7m + 28 + 20m
-25m - 3 = 27m + 28
-32 = 52m
m = -8/13 (this is the simplified form of -32/52)
2006-11-06 12:15:11
·
answer #6
·
answered by Evan L 2
·
0⤊
0⤋
Move the m's to the LHS,
2m-27m-7m-20m=28+3
-52m=31
m=-31/52
2006-11-06 12:14:11
·
answer #7
·
answered by mathpath 2
·
0⤊
0⤋
2m-27m+3=7m+28+20m
-25m+3=27m+28
+25m +25m
3=52m+28
-28 -28
-25=52m
/52 /52
Answer: m= -25/52
2006-11-06 12:20:32
·
answer #8
·
answered by jyar 2
·
0⤊
0⤋
2m-3*9m+(-3*1)=7m+4*7+(4*5m)
2m-27m-3=7m+28+20m
-25m-3=28+27m
-25m+25m-3=28+27m+25m
-3=28+52m
-3-28=28-28+52m
-31=52m
then divide both side by 52
2006-11-06 12:20:15
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
2m-27m-3 = 7m +28 +20m
-25m-3=27m+28
52m=-31
m=-31/52
2006-11-06 12:15:18
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋